Cesarean section: An informed choice or an imposed norm? (Research, Society and Development, 2025)
Objective: Cesarean section is a method of childbirth involving surgical intervention. Its high prevalence in Brazil contrasts with the World Health Organization’s recommendation, which considers a cesarean rate between 10% and 15% to be acceptable. This study aimed to identify the external factors influencing the choice of delivery method among pregnant women in the municipality of Alfenas, Minas Gerais. Methods: This was a descriptive, quantitative, and cross-sectional study conducted through an online questionnaire. The study was approved by the Research Ethics Committee of Unifenas (Approval No. 7.294.822/2024). A total of 30 women who had gone through the decision-making process regarding their delivery method participated in the study. Results: Although the sample size was limited, the study revealed that cesarean sections—while clinically necessary in certain cases—are often chosen due to external influences. These include medical guidance, negative experiences in previous deliveries, fear of complications, and fear of labor pain. Conclusion: The findings suggest that, in order to establish a humanized model of care, healthcare professionals should place pregnant women at the center of the decision-making process regarding the mode of delivery. It is essential to ensure access to high-quality information and to provide active listening to address doubts and concerns.